Beyond profit: ESG disclosure, greenwashing skepticism, and sustainability assurance influences on Indonesian Gen Z’s green investments - Alie, Dwiyani; Lim, Melinda; Lindawati, Ang Swat Lin (Edelweiss Applied Science and Technology, 2025)
Indonesia’s Gen Z is now entering their productive age, increasingly shaping sustainable investment trends. However, their strong pro-sustainability attitudes often do not translate into consistent green investment behavior due to concerns over greenwashing and credibility issues. Despite the rising adoption of sustainability reporting, varying trust levels may restrain Gen Z’s confidence in sustainability information and influence their investment decisions. This research explores how ESG disclosure, greenwashing skepticism, and sustainability assurance affect the investment decisions of Generation Z investors in Indonesia, with trust serving as a mediating variable. Adopting a quantitative research design, data were collected through an online survey of Gen Z investors and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that both ESG disclosure and sustainability assurance positively affect investment decisions, whereas greenwashing skepticism shows no significant effect. Trust is also found to partially mediate and strengthen the link between sustainability assurance and investment decisions. Overall, the findings imply that companies targeting Gen Z investors should prioritize ESG disclosure and seek credible third-party assurance to promote sustainable investment among the younger generation in Indonesia.